The Digital Image Compression Using Wavelet Daubechies Transform - Maitimu, Meldry W; Rumlawang, Francis Y; Tilukay, Meilin I; Batkunde, Harmanus (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2024)
As a form of data representation, the obstacle faced when using digital images is the large volume of data required to represent the image. For that we need a technique that can reduce the volume of data, this thechnique is called compression. In this thesis, a very well-known wavelet transform method is chosen, namely Daubechies D4 wavelet transform, with four coefficients of scaling function, and four coefficients of wavelet function. Then implemented with MATLAB 2021 software as a programming tool to see the effect of quality on the transformed image.